2018
DOI: 10.1080/09540121.2018.1468015
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum maternal mental health is associated with cognitive development of HIV-exposed infants in Zimbabwe: a cross-sectional study

Abstract: This study examines the cognitive profiles of infants born to HIV positive mothers in Zimbabwe. Caregivers with HIV exposed infants delivered in 30 clinics in two areas of Zimbabwe were recruited to the study. Of the 574 study participants, 562 caregiver-infant dyads with a biological HIV +ve mother and infant aged 0-24 months were interviewed. All infants were tested by a trained administrator for cognitive development on the Mullen Scales of Early Learning (MSEL). The Edinburgh Postnatal Depression Scale and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Similar to previous studies, maternal mental health was negatively associated with child development in the language and visual domains [13,14]. It may be that mental health burdens and stress distract mothers from parenting and child stimulation reducing visual and verbal interactions and may affect the crucial child development steps.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to previous studies, maternal mental health was negatively associated with child development in the language and visual domains [13,14]. It may be that mental health burdens and stress distract mothers from parenting and child stimulation reducing visual and verbal interactions and may affect the crucial child development steps.…”
Section: Discussionsupporting
confidence: 79%
“…Low socioeconomic status is also a known risk factor for poorer cognitive development [88] and is particularly important to consider in the context of HIV infection given the overlaps between HIV/AIDS and economic and food insecurity [9]. Lastly, poor maternal mental health during the pre-and postnatal periods may adversely influence infant neurodevelopmental outcomes [89], and among women living with HIV specifically, depression and mental health vulnerabilities are especially prevalent [90] and have shown to associate with infant health outcomes [91].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HEU children seem to be disadvantaged with respect to birth outcomes such as preterm birth, linear growth, metabolism, adaptive and innate immune systems; and increased infectious morbidity [24]. In addition to direct exposure in utero and during delivery, mothers with HIV-1 can also affect the health situation of their children indirectly through poverty, caregiver insufficiency, unemployment, illness and bereavement [25]. Previous studies have shown that compared to HEU children, children with HIV infection have more negative impacts on their quality of life [26][27][28].…”
Section: Introductionmentioning
confidence: 99%